2014
DOI: 10.1007/s10735-014-9565-4
|View full text |Cite
|
Sign up to set email alerts
|

Sintered anorganic bone graft increases autocrine expression of VEGF, MMP-2 and MMP-9 during repair of critical-size bone defects

Abstract: This study aimed to evaluate morphometrically the bone formation and immunohistochemically the expression of vascular endothelial growth factor (VEGF) and metalloproteinase (MMP)-2 and -9 during the healing of critical-size defects treated with sintered anorganic bone (sAB). The 8-mm diameter full-thickness trephine defects created in the parietal bones of rats were filled with sAB (test group) or blood clot (CSD-control group). At 7, 14, 21, 30, 90 and 180 days postoperatively (n = 6/period) the volume of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
2
16
0
7
Order By: Relevance
“…Using video capture techniques, the trafficking of DC‐STAMP+ cells to fracture sites occurs in an organized order. Collectively, our data suggest that DC‐STAMP, together with MMP‐2 and MMP‐9 (Galliera et al, ; Rocha et al, ), can be a useful tool for monitoring, in parallel with other bone turnover markers, to evaluate bone remodeling and tissue healing. Given that DC‐STAMP+ cells are homing to bone fracture sites, a step forward approach is to molecular engineer a chimeric DC‐STAMP protein by which DC‐STAMP is able to bring small peptides/proteins such as bone morphogenetic protein 2 (BMP‐2) or MMP‐9 (Kim et al, ; Matsumoto et al, ; Miller et al, ; Saito et al, ; Wang et al, ) with healing‐promoting effects to bone fracture sites.…”
Section: Clinical Potentials Of Dc‐stampmentioning
confidence: 57%
“…Using video capture techniques, the trafficking of DC‐STAMP+ cells to fracture sites occurs in an organized order. Collectively, our data suggest that DC‐STAMP, together with MMP‐2 and MMP‐9 (Galliera et al, ; Rocha et al, ), can be a useful tool for monitoring, in parallel with other bone turnover markers, to evaluate bone remodeling and tissue healing. Given that DC‐STAMP+ cells are homing to bone fracture sites, a step forward approach is to molecular engineer a chimeric DC‐STAMP protein by which DC‐STAMP is able to bring small peptides/proteins such as bone morphogenetic protein 2 (BMP‐2) or MMP‐9 (Kim et al, ; Matsumoto et al, ; Miller et al, ; Saito et al, ; Wang et al, ) with healing‐promoting effects to bone fracture sites.…”
Section: Clinical Potentials Of Dc‐stampmentioning
confidence: 57%
“…MMPs and TIMPs are expressed by osteoblasts (21)(22)(23)(24)(25) and play a role in bone development, modeling and remodeling. The present results demonstrated that MMP9 was associated with AOB.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of MMP-9 was further evaluated in a critical size parietal defect in rats comparing spontaneous regeneration and application of sintered anorganic bone grafts. In the control (spontaneous healing) group, protein expression peaked in the first and second weeks after defect generation, and in the study group it M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 peaked at 30 days of healing (Rocha et al, 2014). It has to be taken into consideration that the defect size with regard to the critical size and the application of bone replacement material may also alter the expression on both gene and protein levels.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%